Identity dimensions and life satisfaction of students and workers - Karaś, Dominika; Kłym, Maria; Wasilewska, Żaneta Maria; Rusiak, Dagmara; Cieciuch, Jan (Studia Psychologica: Theoria et praxis, 2012)
The main aim presented study was to examine the relationships between satisfaction with life (Diener, 1984) and five identity dimensions distinguished by Luyckx (Luyckx, Goosens, Soenens, & Beyers, 2006, Luyckx et al., 2008): commitment making, identification with commmitment, exploration in breadth, exploration in depth and ruminative exploration. The participants where 417 students and workers aged 19-17. The results indicated significant relationships between identiti dimensions and life satisfaction and also showed the differences between students and workers group: in student subsample significant appeared to be the connection between in breadth exploration and satisfaction with life, and in workers sub-samplem the connections of life satisfaction and exploration in depth. Moreover, in both sub-samples the significant links between satisfaction with life and ruminative king of exploration were reported. it was also found, that identification with commitment mediates the relation of commitment making anf life satisfaction.